A carta do leitor como reflexo e refração do posicionamento ideológico do jornal - Miranda, André Freitas (2017)
The reader's letter is built at the interlacement of different speech, and so being, its construction process is too complex. The transmission of the other is one of the main characteristics of this genre argumentative and can happen in many ways, resulting in different effects of meaning, according to Bakhtin / Volochínov (2009) be not only a theme of a statement, but constituent and constitutive of it. No however, we realize that newspapers can use of the reader as a rhetorical-discursive strategy to maintain or promote adherence from readers to speeches of the newspaper itself. In fact, this claim could not only be based on the reader's letters, but also on the relation that this genre of argument can establish with different genres of the newspaper and the media, particularly the journalistic. Based on theoretical and methodological assumptions proposed by Bakhtin and his Circle, whose theoretical founding principle conceives that all socio-verbal interaction results in statements that respond to previous statements and elicit new speech, we will observe: how the reader's letter can present youself as a reflection and refraction of the newspaper's ideologicaldiscursive position, analyzing the dialogical process of construction of this genre of argument; your differents ways of transmission of the discourse of others; how this process results in an author-creator engendered dialogically; and what are the characteristics of the reader’s letter as a concrete statement. Because it is a genre argumentative, it was necessary find similar aspects between the bakhtiniana theory, Patrick Charaudeau's Semiolinguistics and the New Rhetoric of Perelman and Olbrechts-Tyteca. The corpus of this research consists of 41 Letters from the newspaper reader "A Tribuna" and "A Gazeta"; being 22 letters published by the newspaper "A Gazeta" between March 2 and April 5, 2015 and 19 letters published by the newspaper "A Tribuna" between March 2 and May 10 2015.